Planning and pricing for decimalisation - Dunbar, David Stuart (London : Gower P., 1969)
The book gives sound factual background, extremely useful for those beginning to study decimalization. It also deals in considerable detail with the problems of pricing under the new system. It has a refreshing approach in that it puts consumer needs high on the list of priorities, and the necessary accounting and machinery changes are also well covered.
includes index
Bibliography: p. 135.
usc 26/05/2017
Loans
Keywords: Money; Decimal system